Faustmann und der Einfluss von Steuern - Hechtner, Frank; Kruschwitz, Lutz; Löffler, Andreas; Möllmann, Torsten (Allgemeine Forst- und Jagdzeitung, 2015)
Comparing normal forest rotations with the rotation periods, resulting from the Faustmann-calculus, it can be seen that the Faustmann model always recommends significantly short cycles. Since a model is always based on a series of simplifying assumptions several causes may be accounted responsible for this discrepancy. Our paper tries to improve the original work of FAUSTMANN (1849) by including personal income taxes in the calculus. In the context of the present German tax regime it is shown that there is only a slight difference between the optimization conditions with and without taxes. It is just a different interest rate which must be employed. This interest rate is the lower the higher the income tax rate. It follows that the rotation periods must be longer in a model with taxes than in a model without taxes. An example shows that this influence is quite large at a sufficiently high tax rate.
CRIS-Team Scopus Importer:2020-08-10
Keywords: Faustmann-calculus; Personal income tax